Psychosocial interventions for the diabetic patient - Harvey JN (Dove Medical Press, 2015)
John N Harvey Diabetes Research Group, Wrexham Academic Unit, Bangor University, Wrexham, UK Abstract: Diabetes usually requires substantial life-long self-management by the patient. Psychological factors and the patient's health beliefs are important determinants of self-care behavior. Education has a modest influence on generating better self-care, but psychologically based interventions are clearly more effective. This review gives an overview of these interventions with some discussion of their basis in psychological theory. Some labels such as cognitive behavioral therapy and family therapy include a wide range of approaches. Randomized trials have generally produced improvement in measures of psychological well-being, but improved glycemic control has been more elusive. The influence on behavior can be very dependent on the individual therapist. Only a few trials have managed to sustain improvement in glycosylated hemoglobin beyond a year. Not all patients are prepared to engage and accept these forms of therapeutic intervention. We are still some way from moving psychological management from the trial situation into the diabetic clinic. Keywords: health beliefs, motivational interviewing, cognitive behavioral therapy, family therapy, adolescence